Determinants of digital financial inclusion in enhancing financial well-being among poor households: Evidence from Malaysia - Lu Ming Pey; Zunarni Kosim; Yong Kang Cheah (Gadjah Mada International Journal of Business, 2026)
This study examines the factors influencing financial well-being and investigates the mediating role of digital financial inclusion among households with incomes below the national poverty line in Malaysia. The study used Partial Least Squares Structural Equation Modelling (PLS-SEM) and Importance-Performance Map Analysis (IPMA) to estimate the results. This study collected 1,171 responses and found that digital literacy, digital financial service infrastructure, and financial service providers were determining factors of digital financial inclusion. Financial service providers and digital financial inclusion showed a significant relationship with financial well-being. Mediation analysis showed that digital literacy, digital financial service infrastructure, and financial service providers indirectly affected financial well-being through digital financial inclusion. The results of the IPMA showed that financial service providers and digital financial inclusion were the most important factors in achieving financial well-being. Furthermore, financial service providers were the key factor of digital financial inclusion in high-poverty states, while digital literacy was a key factor in moderate- and low-poverty states. The study offers insights for policymakers working towards an inclusive society and provides financial service providers with information to design services that meet the needs of poor households. This study also offers important implications for other developing countries in Southeast Asia that share similar socio-economic and digital challenges.